A Matter of Measurement: How Different Ways of Measuring Racial Gaps in School Discipline Can Yield Drastically Different Conclusions About Racial Disparities in Discipline. (June 2020) - Curran, F. Chris
Racial disparities in school discipline remain central to policy discussions around school discipline. Recent research points to the importance of how discipline disparities are measured for the conclusions that are drawn about the extent of the problem or whether such disparities are improving. This brief uses data from Maryland to demonstrate how the choice of metric of the Black-White discipline gap can drastically change conclusions about whether the gap is closing or widening as well as conclusions about whether particular districts or schools have high or low racial disparities in discipline. This brief shows how interpretations of the Black-White discipline gap can be drastically different when using different metrics. Implications for educational researchers and practitioners studying school discipline are given.